2022
DOI: 10.1186/s12933-022-01645-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of stress hyperglycemia ratio and in-hospital mortality in patients with coronary artery disease: insights from a large cohort study

Abstract: Background Stress hyperglycemia is strongly associated with poor clinical outcomes in patients with acute coronary syndrome (ACS). Recently, the stress hyperglycemia ratio (SHR) has been proposed to represent relative hyperglycemia. Studies regarding the relationship between SHR and mortality in coronary artery disease (CAD) are limited. This study aimed to clarify the association between SHR and in-hospital mortality in patients with CAD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…A large cohort study in Asia found a correlation between SHR and early and late cardiac outcomes among ACS patients [ 16 ]. An analysis by Xu et al found a significant association between SHR and in-hospital mortality in patients with CAD [ 18 ]. The SHR significantly predicted all-cause mortality among 5841 STEMI patients and 4105 NSTEMI patients after one year of fellow up [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A large cohort study in Asia found a correlation between SHR and early and late cardiac outcomes among ACS patients [ 16 ]. An analysis by Xu et al found a significant association between SHR and in-hospital mortality in patients with CAD [ 18 ]. The SHR significantly predicted all-cause mortality among 5841 STEMI patients and 4105 NSTEMI patients after one year of fellow up [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The best cut-off value of SHR to predict clinical outcomes in CAD patients differs among studies. Among 19,929 patients with CAD, 0.741 was the best cut-off value for SHR to predict clinical outcomes [ 18 ]. An optimal SHR cut-off value of 0.78 predicted poor prognosis in ACS patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also confirmed that relative hyperglycemia measured by SHR was more associated with critical illness than absolute hyperglycemia and was a better biomarker for critical illness than absolute hyperglycemia [ 12 ]. Moreover, overwhelming evidence substantiates that SHR is significantly related to adverse cardiovascular outcomes and related mortality [ 11 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%